Predicting the Factors of Employee Agility Using Enterprise Social Media: The Moderating Role of Innovation Culture - Zhang, Luteng; Xu, Yan; Chen, Chunchun; Zhao, Rui (Frontiers in Psychology, 2022)
This study aims to create a research model that examines how employee agility is affected by enterprise social media usage (ESMU), and to discuss the moderating role of innovation culture in communication quality, trust, and employee agility using the relational capital theory. Data of 477 Chinese employees from different companies were collected in this study for analysis, and the hypotheses developed were examined. The purpose of this study was to explore the influence mechanism that propels employees’ ESMU, communication quality and trust and the moderating effect of innovation culture. This study conducts PLS-SEM to analyze collected data. The results show that ESMU is positively associated with communication quality and trust; innovation culture plays a positive moderating role in ESMU and employee agility; and high communication quality and trust can lead to high agility. However, innovation culture does not have a remarkable moderating effect on ESMU and communication quality. This study offers empirical evidence on how the effect of ESMU on employee agility is transferred by innovation culture. In addition, the benefits of enterprise social media for organizational management are also measured in this study, which may motivate the managements to introduce enterprise social media in work spaces.